Pengaruh Pengembangan Mutu Karyawan, Komitmen Organisasi, dan Efektivitas Pengendalian Internal Terhadap Pencegahan Kecurangan: (Studi Kasus LPD Kecamatan Seririt) - Desy Kristina; I Gede Putu Banu Astawa (Jurnal Akuntansi Profesi, 2022)
The study aims to find out how variable employee quality development, organization commitment, and internal control effectiveness affect prevention. The study was conducted with a quantitative method. The population which is the unit for analysis in this study is 19 pd in the sheath district. How the sample is taken is by an impressive sampling with the number of respondents to 51. The type of data in this study is the primary data and secondary data.  Data collection is done using a questionnaire's instrument. The measurement was conducted through a Likert scale. The research data analysis was throough multiple linear regression analysis of SPSS Version 24.0. The results of this study were as follows: employee quality, organization commitment, and the effectiveness of internal control affect cheating prevention, an independent variable contribution is 70.9%.Keywords: MSME, Pentahelix, Collaboration Keywords : Employee Quality, Organizational Commitment, Internal Control Fraud Prevention